Electing the President of the European Commission - GALLAGHER, MICHAEL; MARSH, MICHAEL ANTHONY; Singh, Robert; Tonra, Ben; Laver, Michael (Trinity College Dublin, 1995)
This paper is concerned with the legitimacy and accountability of decision-making in the European Union (EU). In the first half of the paper we argue that a straightforward and effective way to improve the legitimacy and accountability of EU decision making is to introduce popular elections for the office of European Commission President (ECP). These elections would engage European citizens directly and transparently in the affairs of the Union as it moved towards the twenty-first century, by involving them in a major election for high EU office. Other solutions either do not go far enough in terms of giving European citizens a say or are obscure, cumbersome and/ or contrary to the EU method of doing business. In the second half of the paper the authors drive towards specific proposals for the popular election of the ECP. Three key elements of these proposals are: the nomination process; the election system; and protecting the interests of smaller member states.
PUBLISHED
Keywords: Public Policy; Electoral system; European Commission